Periodically poled lithium niobate ridge waveguides with high conversion efficiency for 2f‐to‐3f self‐referencing interferometer. Issue 2 (1st January 2013) - Hitachi, K.; Ishizawa, A.; Nishikawa, T.; Asobe, M.; Sogawa, T.
Abstract : The generation of second‐ and third‐harmonic light with single‐ and dual‐pitch periodically poled lithium niobate ridge waveguides for achieving a carrier‐envelope‐offset‐locked frequency comb with low pulse energy is investigated. The wavelengths of both the second‐ and third‐harmonic light converted by short‐ and long‐wavelength components of supercontinuum spectra are precisely adjusted by selecting appropriate pitch size and controlling the temperature of the devices. The output powers of the second‐ and third‐harmonic light are 9.1 and 4.8 µW, respectively, when using a 2/3‐octave‐wide supercontinuum light generated by a 1.2 nJ laser pulse at a repetition rate of 250 MHz.